IMPLEMENTASI STRATEGI BRANDING PRODUK BY.U MELALUI KEGIATAN KONSER DI SURABAYA DALAM MENINGKATKAN BRAND AWARENESS - Joy Verna Detta Br Regar; Lia Nirawati (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this study is to examine how by.U's product branding strategy is being implemented through musical events in Surabaya in order to raise consumer awareness of the brand, particularly among younger customers. Building brand awareness in a highly competitive industry is a problem for By.U, a digital telecoms service provider. To grab the target audience's attention, the firm uses a variety of tactics, such as hosting music events featuring well-known performers and influential people. In-depth interviews and observations of concert events hosted by.U. in Surabaya are the methods used to gather data for this qualitative case study study. The findings demonstrate that musical events have the potential to greatly raise brand recognition and improve by.U product perceptions among consumers. The concert's active engagement of the younger generation fosters a deep emotional bond with the brand, raising customer awareness and loyalty. However, this study also discovered that regular review of the promotional activities conducted and consistency in branding techniques are necessary to continue the good impact. This study offers valuable insights for other businesses looking to raise brand recognition through major events and significantly advances the development of experiential marketing techniques in the telecom sector.